Mathematical modeling of the aerodynamic coefficients of a sail blade - Tleubergenova, A.Zh.; Tanasheva, N.K.; Shaimerdenova, K.M.; Kassymov, S.S.; Bakhtybekova, A.R.; Shuyushbayeva, N.N.; Uzbergenova, S.Zh.; Ranova, G.A. (Advances in Aerodynamics, 2023)
The authors of the work numerically studied the aerodynamic coefficients of the sail blade, during which the patterns of three-dimensional flow around airflow and the pressure distribution field were obtained. The triangular sail blade is used as the power element of wind turbines. The sail blade modeling was based on the Reynoldsaveraged Navier–Stokes equations (RANS) using the ANSYS FLUENT computer program. A flow pattern is obtained, which gives a physical explanation of the nature of the airflow around the sail blade and the pressure distribution field. Comparative analyses of theory and experiment are given. In the range of Reynolds numbers from 0.5 × 104 to 2.5 × 104, the change in the drag force coefficient is from 1.04 to 0.54, and the difference in the lift force coefficient is from 0.52 to 0.33.
Keywords: Sail blade; Wind turbine; Modeling; ANSYS FLUENT; Aerodynamic coefficients